2007
DOI: 10.1158/1078-0432.ccr-06-3091
|View full text |Cite
|
Sign up to set email alerts
|

Functional Up-regulation of Human Leukocyte Antigen Class I Antigens Expression by 5-aza-2′-deoxycytidine in Cutaneous Melanoma: Immunotherapeutic Implications

Abstract: Purpose:To investigate the potential of the DNA hypomethylating agent 5-aza-2 ¶-deoxycytidine (5-aza-CdR) to improve the effectiveness of immunotherapeutic approaches against melanocyte differentiation antigens. Experimental Design: The effect of 5-aza-CdR on the constitutive expression of gp100 was investigated in 11human melanoma cell lines by real-time reverse transcription-PCR and indirect immunofluorescence (IIF) analyses. 5-aza-CdR^mediated changes in the levels of expression of human leukocyte antigen (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(84 citation statements)
references
References 38 publications
3
79
0
2
Order By: Relevance
“…This observation is particularly appealing in view of the demonstration that the upregulation of HLA class I antigens induced by 5-AZA-CdR was per se sufficient to improve gp 100-specific cytotoxic T cell recognition of melanoma cells. 5 In addition, loss of expression of HLA class I molecules by tumor cells has been recently suggested to represent a mechanism of tumor resistance that can develop during CTLA-4 therapy with ipilimumab. 21 Therefore, the upregulation of HLA class I molecules induced by DNA hypomethylating agents in vivo could contribute to: (i) improve immune-recognition of neoplastic cells; (ii) recover the efficacy of CTLA-4 blockade in patients progressing to treatment due to down-regulation of HLA class I molecules on tumor cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation is particularly appealing in view of the demonstration that the upregulation of HLA class I antigens induced by 5-AZA-CdR was per se sufficient to improve gp 100-specific cytotoxic T cell recognition of melanoma cells. 5 In addition, loss of expression of HLA class I molecules by tumor cells has been recently suggested to represent a mechanism of tumor resistance that can develop during CTLA-4 therapy with ipilimumab. 21 Therefore, the upregulation of HLA class I molecules induced by DNA hypomethylating agents in vivo could contribute to: (i) improve immune-recognition of neoplastic cells; (ii) recover the efficacy of CTLA-4 blockade in patients progressing to treatment due to down-regulation of HLA class I molecules on tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Exposure of neoplastic cells to these agents effectively improved T cell recognition of melanoma and renal carcinoma cells in vitro. [3][4][5] This functional effect was found to be mediated, at least in part, by the upregulation of the expression of tumor antigens (e.g., Cancer Testis Antigens), HLA class I and accessory/co-stimulatory molecules by neoplastic cells. 3,4,6,7 To further explore the immunomodulatory potential of DNA hypomethylating agents, we also demonstrated that changes in genome-wide expression profiles induced by 5-AZA-CdR in BALB/c mice grafted with the murine mammary adenocarcinoma TS/A cells were preferentially observed in neoplastic tissues as compared to normal counterparts, and that they affected mainly immunologic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Важно, что приобретенные фенотипические изменения он-котрансформированных клеток поддерживаются популяциями опухолевых клеток и функционально значимы, индуцируя или существенно усиливая их распознавание СТА-специфичными ЦТЛ [46,47]. Fonsatti et al [48] продемонстрировали, что после ДГА-терапии одного только изменения уровня антигенов HLA класса I и CD54 на по-верхности клеток меланомы достаточно, чтобы существенно повысить их распознавание антиген-специфичными ЦТЛ.…”
Section: ста и эпигенетические препаратыunclassified
“…Additionally, some chemo drugs can modulate the expression of tumor antigens and antigen processing/presentation machinery on tumor cells. For example, 5-Fluorouracil (5-FU) has been shown to induce carcinoembryonic antigen (CEA) expression in colon and breast cancer cells (Correale et al, 2003) while 5-aza-2'-deoxycytidine can induce the expression of cancer testis antigens and the cell surface MHC class I complex in melanoma and other cancers (Adair & Hogan, 2009;Coral et al, 2002;Fonsatti et al, 2007;Natsume et al, 2008). Notably, direct intralesional injection of the MHC class I complex, which allows tumor immune evasion when defective in numerous cancers (Lampen & van Hall, 2011;Maleno et al, 2011), via high-dose Allovectin-7 ® (Vical Inc., San Diego, CA, USA), a cationic lipid-formulated bicistronic plasmid encoding MHC-I components -2 microglobulin and HLA-B7, in 127 recurrent or previously unresponsive to chemotherapy stage III and IV melanoma patients tested for efficacy in a recent phase II dose escalation study produced an objective response of 11.8% with median duration of response of 13.8 months (Bedikian et al, 2010).…”
Section: Introductionmentioning
confidence: 99%